Interaction between Mesenchymal Stem Cells and the Immune System in Rheumatoid Arthritis - Darina Bačenková; Marianna Trebuňová; Radoslav Morochovič; Erik Dosedla; Alena Findrik Balogová; Petra Gašparová; Jozef Živčák (MDPI AG, 2022)
Rheumatoid arthritis (RA) is an autoimmune disease that causes damage to joints. This review focuses on the possibility of influencing the disease through immunomodulation by mesenchymal stem cells (MSCs). There is an occurrence of rheumatoid factor and RA-specific autoantibodies to citrullinated proteins in most patients. Citrulline proteins have been identified in the joints of RA patients, and are considered to be the most suitable candidates for the stimulation of anti-citrulline protein antibodies production. Fibroblast-like proliferating active synoviocytes actively promote inflammation and destruction in the RA joint, in association with pro-inflammatory cells. The inflammatory process may be suppressed by MSCs, which are a population of adherent cells with the following characteristic phenotype: CD105+, CD73+, CD90+, CD45−, CD34− and HLA DR−. Following the stimulation process, MSCs are capable of immunomodulatory action through the release of bioactive molecules, as well as direct contact with the cells of the immune system. Furthermore, MSCs show the ability to suppress natural killer cell activation and dendritic cells maturation, inhibit T cell proliferation and function, and induce T regulatory cell formation. MSCs produce factors that suppress inflammatory processes, such as PGE2, TGF-β, HLA-G5, IDO, and IL-10. These properties suggest that MSCs may affect and suppress the excessive inflammation that occurs in RA. The effect of MSCs on rheumatoid arthritis has been proven to be a suitable alternative treatment thanks to successful experiments and clinical studies.